457. STANDARDIZATION AND SHORT-TERM RESULTS OF ROBOT-ASSISTED THORACOSCOPIC ESOPHAGECTOMY. (24th September 2022) - Koyanagi, Kazuo; Kazuno, Akihito; Yamamoto, Miho; Higuchi, Tadashi; Yatabe, Kentaro; Kanamori, Kohei; Tajima, Kohei; Nakamura, Kenji; Nabeshima, Kazuhito; Ogimi, Mika
Abstract: Surgical cases of robot-assisted thoracoscopic esophagectomy (RAMIE) is increasing because of the advantages of robotic system. We introduced RAMIE in 2019 and standardized the surgical procedure. The usefulness of RAMIE was examined by classifying surgical cases into early and late periods and comparing the surgical results. Fifty-four patients who underwent RAMIE were enrolled in the study. All patients underwent D2 or higher lymph node (LN) dissection, gastric tube reconstruction, and R0 surgery. The patients were divided into two groups, 26 cases in the first half up to December 2020 and 28 cases in the second half after January 2021. The patient background, surgical technique, and short-term results were compared. The tumor staging was based on the UICC 8th version. Thoracic surgery time was 274 minutes, the chest bleeding volume was 30 mL, and the postoperative hospital stay was 19 days (median). In the late stage, patients with clinical thoracic LN metastasis (p = 0.01) and advanced stage (p = 0.006) were higher than those in the early period. There were significantly more cases of thoracic duct resection and D3 dissection in the late period (p = 0.02, p = 0.009). No differences in postoperative complications and intra-hospital death was observed, however the postoperative hospital stay was significantly shortened in the late period (p = 0.001). Thorough mediastinal LN dissection by RAMIE could be safely performed by standardizing and improving the surgical procedures. RAMIE has several issues such as higher cost associated with equipment and longer operative time, but it is possible to perform precise procedures with solo surgery, and it is expected that cost reduction effects will be expected in terms of the number of participants in surgery and the length of hospital stay after surgery.